2014
DOI: 10.1038/ijir.2013.51
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function in women with primary and secondary infertility in comparison with controls

Abstract: Infertility is a distressing health condition that has diverse effects on couples' lives. One of the most affected aspects of life in infertile women is sexual function, which is a key factor in physical and marital health. The goal of this study was to evaluate sexual function according to the type of infertility in comparison with controls. In this study, 191 women with primary infertility and 129 with secondary infertility along with 87 age-matched healthy controls were enrolled. They were asked to fill a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 13 publications
0
37
1
4
Order By: Relevance
“…The literature on sexual well-being for women with primary vs secondary infertility has shown conflicting results. Some studies have reported higher levels of sexual dysfunction with secondary infertility10, 12; however, other studies have reported improved emotional state and better social relationships with secondary infertility 14 . The difficulty in comparing our study with those cited is that many other studies have included broad outcome measurements that take into account the social, marital, and personal impacts of infertility.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…The literature on sexual well-being for women with primary vs secondary infertility has shown conflicting results. Some studies have reported higher levels of sexual dysfunction with secondary infertility10, 12; however, other studies have reported improved emotional state and better social relationships with secondary infertility 14 . The difficulty in comparing our study with those cited is that many other studies have included broad outcome measurements that take into account the social, marital, and personal impacts of infertility.…”
Section: Discussionmentioning
confidence: 74%
“…Linear variables such as duration of infertility were grouped to make all variables categorical for the regression analysis. In addition, we included duration of marriage and previous biological child because those have been shown to affect sexual well-being 10, 12, 14. Although actual and perceived infertility etiologies were statistically different from each other (χ 2  = 214, P < .01), we judged that the perceived infertility etiology might better reflect the psychosocial state of the participant and therefore be a better predictor of sexual impact.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…kadınlarda intihar girişimi sağlıklı kadınlara göre iki kat daha fazla görülmektedir. [18] Yaşanılan tüm bu psikososyal ve duygusal zorlanmalar nedeniyle infertil kadınların fertil kadınlara göre yaşam kalitesi daha düşük olmaktadır. Özellikle kadınlığın doğurganlık ile özdeşleştirildiği toplumlarda infertilite tanısı, sosyal izolasyona, stigma duygusuna ve özgüven kaybına neden olmaktadır.…”
Section: İnfertil Bireylerin Yaşam Kalitesine Etki Eden Faktörlerunclassified